L’eros e il desiderio. Tradurre l’intraducibile? (ENTHYMEMA, 2019)
Introduction to the annual supplement “Volti del tradurre” edited by Helena Aguilà Ruzola and Donatella Siviero. The section includes a selection of papaers presented at the 5th International Translation Day, held on 3-4 December 2018 at the University of Catania, in collaboration with the Universitat Autònoma de Barcelona and the University of Messina.
Keywords: translation; eros; desire